Die Mitglieder des Petrograder Militär-Revolutionären Komitees, Oktober 1917 - März 1918. From: X B/100
Die Mitglieder des Petrograder Militär-Revolutionären Komitees, Oktober 1917 - März 1918. From: X B/100.